Exposure to natural dew or sprayed water as alternative methods of flower sterilization in indica rice - FAN Long-jiang; WU Jian-guo; SHI Chun-hai; YE Wei-zhong; WU Yue-you (浙江大学学报. 农业与生命科学版)
Two new methods for sterilizing the flowers of indica rice were investigated at different seasons. Two thirds of the lemmas from glumes on a panicle were trimmed away in the afternoon during rice anthesis. One of the methods was to expose the panicles to dews during the night while the other was to spray water over the panicle. The seed setting rates following treatment in the two methods were 2.1% and 2.8% and the cross-fertility rates were 34.2% and 29.2%, respectively. The treatments (dew or water) broke the pollen grains almost into pieces, which was confirmed by observation under light microscope. These two methods are simple, quick and useful alternatives for sterilization of flowers in rice.